2018
DOI: 10.1111/andr.12497
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase clostridium histolyticum for the treatment of Peyronie's disease: a prospective Italian multicentric study

Abstract: Peyronie's disease (PD) is a common condition which results in penile curvature making sexual intercourse difficult or impossible. Collagenase clostridium histolyticum (CCH) is the first licensed drug for the treatment of PD and is indicated in patients with palpable plaque and curvature deformity of at least 30° of curvature. However, only few monocentric studies are available in the current literature and this is the first national multicentric study focusing on this new treatment. In five Italian centres, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…In addition, the authors highlighted the reduction of costs and duration of treatment (Abdel Raheem, Capece, et al, ; Abdel Raheem, Johnson, Abdel Raheem, Capece, & Ralph, ). These results were subsequently confirmed in a recent prospective Italian multicentric study (Capece et al, ). The authors who proposed this protocol have published data regarding the first cycle of three injections, but none of them has evaluated how effective and safe a second cycle could be.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, the authors highlighted the reduction of costs and duration of treatment (Abdel Raheem, Capece, et al, ; Abdel Raheem, Johnson, Abdel Raheem, Capece, & Ralph, ). These results were subsequently confirmed in a recent prospective Italian multicentric study (Capece et al, ). The authors who proposed this protocol have published data regarding the first cycle of three injections, but none of them has evaluated how effective and safe a second cycle could be.…”
Section: Introductionsupporting
confidence: 58%
“…Its safety and efficacy have already been demonstrated in two large RCTs, various retrospective studies, and some authors have also tried to identify predictors of treatment success (Cocci, Russo, Briganti, et al, ; Cocci, Russo, Salonia, et al, ; Gelbard et al, ; Lipshultz et al, ). A standardised protocol of injections has not been established yet, considering that the modified shortened protocol (three injections) has given comparable results to the initial IMPRESS protocol (eight injections; Abdel Raheem, Capece, et al, ; Abdel Raheem, Johnson, et al, ; Capece et al, ). However, there is a minority of patients who may not be completely satisfied after three injections and may want to receive a second cycle of three injections.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery remains the gold standard treatment option for patients with stable PD, it is not recommended for men in the active phase. On the other hand, collagenase clostridium histolyticum (CCH) represents the only licensed drug for the minimally invasive treatment of PD [14,15], however the acute phase of PD is not currently an indication for CCH therapy [3,16,17]. Four studies [18][19][20][21] demonstrated significant improvements in penile curvature after 10 or 15 mg intralesional verapamil, although the protocols varied widely, ranging from 6 to 12 injections.…”
Section: Discussionmentioning
confidence: 99%
“…The only other mechanical therapy that has been reported in conjunction with CCH is the use of vacuum erection devices (VEDs). 21,22 However, because these series did not include a non-VED comparison arm, whether VED resulted in greater improvements over CCH alone is unclear. Thus, the present study is the first to report benefits of adjunctive mechanical therapy on improving CCH outcomes and demonstrates the greatest overall curvature and length improvements of any adjunctive therapy reported to date.…”
Section: Discussionmentioning
confidence: 99%